Prospects and challenges facing frontier stock markets in the western balkans: Quo vadis? - Julia St. Stefanova (Financial Studies, 2019)
The aim of the research paper is to present empirical results on a tested framework of factors influencing selected frontier stock markets of the Western Balkan countries in their accession path to the European Union. These stock markets are juxtaposed with the frontier stock mar ket of Bulgaria - a country full member of the EU in the course of 11 years now, th ereby inferring important comparative conclusions. Based on the comparative analysis between the capital markets in Southern and Eastern Europe (including that of Bulgaria), the paper proposes tentative insights into the road ahead for future regional inte gration and financial development of the capital markets of the Western Balkans.
Keywords: G10; G23; G28; 330; frontier stock markets; emerging stock markets; financial integration; financial development